Exploring Clinical Decision Support System in Health-Care Settings – Challenges and Barriers to Implementation – A Literature Review - Syed, Wajid (Asian Journal of Pharmaceutics (AJP), 2022)
A clinical decision support system (CDSS) has been introduced as an important tool in health-care sectors to make the appropriate decision for patients and health-care delivery by health-care professionals. The decision support system (DSS) is comprised electronic software which assists professionals such as physicians and others to make patientspecific assessments for better health-care delivery and health outcome. Although the implementation of CDSS in health care is a challenging and complex process and it was found that their multiple factors and barriers associated with the successful implementation or practice of CDSS in clinical settings both in Saudi Arabia and other countries.